2020
DOI: 10.1371/journal.pone.0244115
|View full text |Cite
|
Sign up to set email alerts
|

Poly(alizarin red S) modified glassy carbon electrode for square wave adsorptive stripping voltammetric determination of metronidazole in tablet formulation

Abstract: Potentiodynamically fabricated poly(alizarin red s) modified GCE was characterized using CV and EIS techniques. In contrast to the cyclic voltammetric response of the unmodified GCE for metronidazole, an irreversible reduction peak with three-folds of current enhancement and reduced overpotential at the poly(alizarin red s) modified GCE showed the catalytic effect of the modifier towards reduction of metronidazole. While observed peak potential shift with increasing pH (4.0–10.0) indicated the involvement of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Accordingly, the calculated K app values shown in Table 3 depict that the K app value of BiGCE is 7.7 times higher than that of the GCE. This indicates that BiGCE has low charge transfer resistance, hence the bismuth modification improved conductivity and the electron transfer rate between a working electrode and solution interface [18] …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Accordingly, the calculated K app values shown in Table 3 depict that the K app value of BiGCE is 7.7 times higher than that of the GCE. This indicates that BiGCE has low charge transfer resistance, hence the bismuth modification improved conductivity and the electron transfer rate between a working electrode and solution interface [18] …”
Section: Resultsmentioning
confidence: 97%
“…As seen in the table, the anodic and cathodic peak currents of BiGCE are 1.2 and 1.19 larger than GCE. This indicated that bismuth modification resulted in an enhanced electron transfer from the [18] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single sensor modified with the conductive polymer poly (alizarin red S) (PARS/GCE), was proposed by Dawit's team. 70 Another series of modifiers are metallic-based compounds like oxides and other derivatives. Darbandi [71][72][73][74][75][76] Among these sensors, it can be observed that the GCE/MoS 2 exhibits the lowest LOD and the widest dynamic range, due to an increased surface area, surface defects, edge effects, and a decreased charge transfer resistance that enables and enhances electron transfer.…”
Section: Electrochemical Sensors Used For the Determination Of Topica...mentioning
confidence: 99%
“…In the literature, the use of different techniques was reported for separation or quantitative MNZ detection in environmental and biological samples, human plasma, drugs, and food products. They include high-performance liquid chromatography [ 11 ], liquid chromatography-tandem mass spectrometric method (LC-MS/MS) [ 12 ], chemiluminescence [ 13 ] fluorescence [ 14 , 15 ], near-infrared spectrophotometry (NIRS) [ 16 ], spectrophotometry [ 17 , 18 , 19 ], voltammetry with chemically modified electrodes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%